2005
DOI: 10.1038/sj.leu.2403627
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of real-time quantitative PCR (RQ-PCR) in AML with t(8;21)

Abstract: Despite the favorable prognosis of patients with acute myeloid leukemia (AML) with t(8;21)(q22;q22) translocation, relapses still occur in about 30% of the cases but no initial factors can strongly predict the risk of relapse. Several recent studies suggest that monitoring minimal residual disease (MRD) may identify patients at risk of relapse. We prospectively monitored AML1-ETO rearrangement by real-time quantitative PCR (RQ-PCR) in 21 patients uniformly treated in our center. Blood (PB) and bone marrow (BM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 27 publications
6
92
1
6
Order By: Relevance
“…Although MRD levels in PB do not reflect MRD levels in BM, MRD information from PB samples still may have prognostic significance. 13,[24][25][26] However, we found no prognostic significance for PB MRD at TP2 with no difference in levels between patients who remained in remission and those who relapsed (data not shown).…”
Section: Mrd In Paired Bm and Pb Samplesmentioning
confidence: 41%
See 1 more Smart Citation
“…Although MRD levels in PB do not reflect MRD levels in BM, MRD information from PB samples still may have prognostic significance. 13,[24][25][26] However, we found no prognostic significance for PB MRD at TP2 with no difference in levels between patients who remained in remission and those who relapsed (data not shown).…”
Section: Mrd In Paired Bm and Pb Samplesmentioning
confidence: 41%
“…23 In contrast, two adult MRD studies reported comparable MRD levels between BM and PB. 24,25 The reasons for these discrepancies are not clear, but technical variance seems unlikely and differences in biology of the leukemic cells may be an explanation. Although MRD levels in PB do not reflect MRD levels in BM, MRD information from PB samples still may have prognostic significance.…”
Section: Mrd In Paired Bm and Pb Samplesmentioning
confidence: 99%
“…The value of quantitative PCR for the determination of the minimal residual disease (MRD) load was confirmed in numerous previous studies, [18][19][20] and recent molecular markers such as the NPM1 mutations in AML [21][22][23] and the JAK2V617F in the CMPD [24][25][26][27] might further contribute to the spectrum of follow-up markers in the post transplant period. 6,28 Novel molecular methods-for example, on the basis of quantitative PCR-provide the opportunity of higher sensitivity for chimerism analyses.…”
Section: Introductionmentioning
confidence: 72%
“…Quantitative PCR monitoring in AML is best validated for the reciprocal gene fusions t(15;17)/PML-RARA, inv(16)/CBFB-MYH11 and t(8;21)/ AML1-ETO with sensitivities ranging from 10 À4 to 10 À6 , 20,[83][84][85] as the score of the aberrant gene expression compared after consolidation therapy and at diagnosis has a significant prognostic impact, 19 and distinct thresholds of transcript copy numbers were determined to correlate with an increased relapse risk. 84,85 The interval between the increase of the respective fusion transcripts and the clinical manifestation of relapse can be as long as 3-6 months.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…5 The score of the aberrant gene expression compared after consolidation therapy and at diagnosis was shown to be significantly associated with survival. 124 Persistence 52 or minor decrease of transcript copy numbers 5 predicts an enhanced relapse risk. A threshold of p1% of the initial mutated cell load was determined to correlate with an increased relapse risk in patients with core binding factor leukemias 125 and in another study a transcript number of 410 during follow-up was found to correlate with significantly shortened OS in inv(16) cases.…”
Section: Minimal Residual Disease Diagnosticsmentioning
confidence: 99%